2018
DOI: 10.1037/xge0000402
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the balance between goals and habits: Five failures in experimental habit induction.

Abstract: Habits are repetitive behaviors that become ingrained with practice, routine, and repetition. The more we repeat an action, the stronger our habits become. Behavioral and clinical neuroscientists have become increasingly interested in this topic because habits may contribute to aspects of maladaptive human behavior, such as compulsive behavior in psychiatry. Numerous studies have demonstrated that habits can be induced in otherwise healthy rats by simply overtraining stimulus–response behaviors. However, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
192
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(230 citation statements)
references
References 60 publications
(124 reference statements)
25
192
3
Order By: Relevance
“…Whether maladaptive behaviors characteristic of drug abuse are supported by enhancements in habit memory systems, impairments in goal-directed memory systems or a combination of both remains poorly understood (de Wit et al, 2018;Ersche et al, 2016;Everitt & Robbins, 2005;Robbins et al, 2008).…”
mentioning
confidence: 99%
“…Whether maladaptive behaviors characteristic of drug abuse are supported by enhancements in habit memory systems, impairments in goal-directed memory systems or a combination of both remains poorly understood (de Wit et al, 2018;Ersche et al, 2016;Everitt & Robbins, 2005;Robbins et al, 2008).…”
mentioning
confidence: 99%
“…This manipulation might conceivably have diluted the effect of repetition owing to the different number of instrumental contingencies experienced before the relevant critical test across subjects. Furthermore, the short task duration may have limited the possibility of detecting training effects, in line with evidence that limited overtraining in instrumental behaviors often fails to produce habit learning (46) .…”
Section: Discussionmentioning
confidence: 86%
“…Three studies have demonstrated that the drug-seeking response is initially goal-directed but then becomes habitual with extended training [69][70][71]. However, because food seeking also transitions from goal-directed to habitual control with training in animals [187] (not replicated in humans [188]), these findings do not inform us about the unique habit forming potential of drug seeking.…”
Section: Studies With Laboratory Animalsmentioning
confidence: 99%